Pooling Risk Among Countries - Imbs, Jean (IMF Working Papers; Working Paper ;, 2007)
In this paper, we identify the groups of countries where international risk-sharing opportunities are most attractive. We show that the bulk of risk-sharing gains can be achieved in groups consisting of as few as seven members, and that further marginal benefits quickly become negligible. For many such small groups, the welfare gains associated with risk sharing can amount to one order of magnitude larger than Lucas's classic calibration suggested for the United States, under similar assumptions on utility. Why do we not observe more arrangements of this type? Large welfare gains can only be achieved within groups where contracts are probably seen as relatively difficult to enforce. International diversification can thus yield substantial gains, but these may remain untapped owing to potential partners' weak institutional quality and a history of default on international obligations. Noting that existing risk sharing arrangements often have a regional dimension, we speculate that shared economic interests such as common trade may help sustain such arrangements, though risk-sharing gains are smaller when membership is constrained on a regional basis.